Exploring offender manager's experiences of psychologically informed consultation on relationships with service users within the offender personality disorder pathway. Issue 4 (24th September 2020) - Radcliffe, Kay; Carrington, Bethany; Ward, Max
Abstract : Purpose: The Yorkshire and Humber Personality Disorder Partnership (YHPDP) provides psychological consultation and formulation to offender managers (OMs) within the National Probation Service as part of the offender personality disorder (OPD) pathway. The pathway highlights the importance of formulation-led case management to develop pathways for offenders with personality difficulties at high risk of causing serious harm to others. This study aims to ask what is the experience of psychological consultation/formulation on the relationship between a sample of service users (SUs) and their OMs. Design/methodology/approach: Semi-structured interviews were undertaken with five OMs who had engaged in at least three consultations with YHPDP psychologists/psychotherapists within the OPD pathway. Qualitative methods were used to analyse the data, specifically interpretative phenomenological analysis, which is useful when dealing with complexity, process or novelty. Findings: OMs experienced the consultation/formulation process to be containing and reflective. They found complex, emotionally demanding clients who have offended and have personality disorder traits could be responded to differently as a result of this process. From an OM perspective, this improved the relationship between themselves and their SUs and supported risk management. These conclusions must be tentative, as they are drawn from a small-scale qualitative study, but provides the basis for further research. Originality/value: Although there is increasing research into the outcomes of the OPD pathway, little has been done regarding the experience of the relationship between OMs and SUs. This research takes a qualitative perspective to explore this area.